Mennonite in a little black dress (Colorado State Library Book Club Collection): a memoir of going home (Henry Holt and Co, 2009)
A hilarious and moving memoir--in the spirit of Anne Lamott and Nora Ephron--about a woman who returns home to her close-knit Mennonite family after a personal crisis.
The bridegroom cousin , Touch my tooth , Fear of mosquitoes , Wounding words , A lingering finish , What the soldier made , The big job , Rippling water , Wild thing , The trump shall sound , And that's okay! , The raisin bombshell , The therapeutic value of lavender , Appendix : A Mennonite history primer

Erené with wolf medicine (Prickly Pear Publishing, 2022)
"Dr. Irene Blea pens a heart-rending autobiography of a young girl's journey moving from the spiritual center of her small ranch in northern New Mexico to the gritty steel town of Pueblo Colorado. Leaving behind an extended family immersed in the rich Indigenous and Spanish customs of Hispano peoples, Irene boldly reckons with the economic, racial, and gender dislocations of modern society. Her compelling story of "renacimiento" or rebirth reveals a profoundly nurturing remedy for marginalization, oppression, and self-alienation. Irene's narrative will inspire generations of women to harness their life forces and spiritual destinies to generate self-love and empowerment. For Irene, it is in the strength of the wolf that she sees her reflection and accepts the solemnity of life"--

Rough beauty (Colorado State Library Book Club Collection): forty seasons of mountain living (Scribner, 2018)
"In the bestselling tradition of Cheryl Strayed's Wild and Helen MacDonald's H Is for Hawk, a stunning, inspirational memoir from an award-winning poet who ventures into the wilderness to seek answers to life's big questions and finds her way back after losing everything she thought she needed"--
Prologue: The hard prayer , Part I. Marlboro woman , Good girl , Saying no , Marlboro woman , Part II. Refuge , Summer into fall , Winter , Spring , Summer , Part III. Home of the somewhat feral , Controlled burn , Home of the somewhat feral , Fuck T.S. Eliot , The book of mornings , Part IV. A season of voluptuousness , Loving Elvis , Yajna: fire ceremony , A season of voluptuousness , Epilogue: The fox who came to dinner.

A bookshop in Berlin (Colorado State Library Book Club Collection): the rediscovered memoir of one woman's harrowing escape from the Nazis (Atria Books, 2019)
In 1921, Françoise Frenkel-a Jewish woman from Poland-fulfills a dream. She opens La Maison du Livre, Berlin's first French bookshop, attracting artists and diplomats, celebrities and poets. The shop becomes a haven for intellectual exchange as Nazi ideology begins to poison the culturally rich city. In 1935, the scene continues to darken. First come the new bureaucratic hurdles, followed by frequent police visits and book confiscations. Françoise's dream finally shatters on Kristallnacht in November 1938, as hundreds of Jewish shops and businesses are destroyed. La Maison du Livre is miraculously spared, but fear of persecution eventually forces Françoise on a desperate, lonely flight to Paris. When the city is bombed, she seeks refuge across southern France, witnessing countless horrors: children torn from their parents, mothers throwing themselves under buses. Secreted away from one safe house to the next, Françoise survives at the heroic hands of strangers risking their lives to protect her.
A French bookshop in Berlin , Paris , Avignon , Vichy , Nice , Somewhere in the mountains , Return to Nice , Grenoble , At the border , Annecy , Saint-Julien , Annecy , At the border , Heading for Switzerland.

Red notice: a true story of high finance, murder, and one man's fight for justice (Colorado State Library Book Club Collection) (Simon & Schuster, 2015)
A real-life political thriller about an American financier in the Wild East of Russia, the murder of his principled young tax attorney, and his dangerous mission to expose the Kremlin's corruption.
Persona non grata , How do you rebel against a family of communists? , Chip and Winthrop , "We can get you a woman to keep you warm at night" , The bouncing Czech , The Murmansk trawler fleet , La Leopolda , Greenacres , Sleeping on the floor in Davos , Preferred shares , Sidanco , The magic fish , Lawyers, guns, and money , Leaving Villa d'Este , And we all fall down , Tuesdays with Morrie , Stealing analysis , Fifty percent , A threat to national security , Vogue Caf℗♭℗ʺ , The G8 , The raids , Department K , "But Russian stories never have happy endings" , High-pitched jamming equipment , The riddle , DHL , Khabarovsk , The ninth commandment , November 16, 2009 , The Katyn Principle , Kyle Parker's war , Russell 241 , Russian untouchables , The Swiss accounts , The tax princess , Sausage making , The Malkin delegation ; Justice for Sergei , Humiliator, humiliatee , Red notice , Feelings.

Let me tell you what I mean (Colorado State Library Book Club Collection) (Vintage Books, a division of Penguin Random House LLC, 2022)
From one of our most iconic and influential writers: twelve pieces that offer an illuminating glimpse into the mind and process of a legendary figure. These essays from 1968 to 2000, which have not been gathered together until now, showcase Joan Didion's incisive reporting, her empathetic gaze, and her insights on writing. They touch on subjects ranging from newspapers ("the problem is not so much whether one trusts the news as whether one finds it"), to the fantasy of San Simeon, to not getting into Stanford. In "On Being Unchosen by the College of One's Choice," Didion ponders the fraught parent/child dilemma: "I wonder if we had better not find some way ... to extricate our expectations from theirs...to let them work through their own rejections." From her admiration for Hemingway's sentences to her acknowledgement that Martha Stewart's story is one "that has historically encouraged women in this country, even as it has threatened men," these pieces are acutely and brilliantly observed. This timeless collection of Didion's mostly early writing reveals what would become her subjects, including the press, politics, California robber barons, women, the act of writing, and her own self-doubt. Each piece is classic Didion: incisive, bemused, and stunningly prescient--From dust jacket. "From one of our most iconic and influential writers: twelve pieces that offer an illuminating glimpse into the mind and process of a legendary figure. These essays from 1968 to 2000, which have not been gathered together until now, showcase Joan Didion's incisive reporting, her empathetic gaze, and her insights on writing.From her admiration for Hemingway's sentences to her acknowledgement that Martha Stewart's story is one 'that has historically encouraged women in this country, even as it has threatened men,' these pieces are acutely and brilliantly observed. This timeless collection of Didion's mostly early writing reveals what would become her subjects, including the press, politics, California robber barons, women, the act of writing, and her own self-doubt. Each piece is classic Didion: sharp, bemused, and stunningly prescient."--From page 4 of printed paper wrapper.
(from table of contents) Foreword / by Hilton Als --, Alicia and the underground press --, Getting serenity --, A trip to Xanadu --, On being unchosen by the college of one's choice --, Pretty Nancy --, Fathers, sons, screaming eagles --, Why I write --, Telling stories --, Some women --, The long-distance runner --, Last words --, Everywoman.com.

Infidel (Colorado State Library Book Club Collection) (Free Press, 2008)
The author of The Caged Virgin recounts the story of her life, from her traditional Muslim childhood in Somalia and escape from a forced marriage to her efforts to promote women's rights while surviving numerous threats to her safety.
Bloodlines , Under the Talal tree , Playing tag in Allah's Palace , Weeping orphans and widowed wives , Secret rendezvous, sex, and the scent of Sukumawiki , Doubt and defiance , Disillusion and deceit , Refugees , Abeh , Running away , A trial by the Elders , Haweya , Leiden , Leaving God , Threats , Politics , The murder of Theo , Epilogue: the letter of the law.

Educated (Colorado State Library Book Club Collection): a memoir (Random House, 2018)
"Tara Westover was seventeen the first time she set foot in a classroom. Born to survivalists in the mountains of Idaho, she prepared for the end of the world by stockpiling home-canned peaches and sleeping with her "head-for-the-hills bag." In the summer she stewed herbs for her mother, a midwife and healer, and in the winter she salvaged in her father's junkyard. The family was so isolated from mainstream society that there was no one to ensure the children received an education, and no one to intervene when one of Tara's older brothers became violent. As a way out, Tara began to educate herself, learning enough mathematics and grammar to be admitted to Brigham Young University. Her quest for knowledge would transform her, taking her over oceans and across continents, to Harvard and to Cambridge. Only then would she wonder if she'd traveled too far, if there was still a way home. With the acute insight that distinguishes all great writers, Tara Westover has crafted a universal coming-of-age story that gets to the heart of what an education offers: the perspective to see one's life through new eyes, and the will to change it."--Provided by publisher.
Choose the good , The midwife , Cream shoes , Apache women , Honest dirt , Shield and buckler , The Lord will provide , Tiny harlots , Perfect in his generations , Shield of feathers , Instinct , Fish eyes , Silence and the churches , My feet no longer touch the earth , No more a child , Disloyal man, disobedient heaven , To keep it holy , Blood and feathers , In the beginning , Recitals of the fathers , Skullcap , What we whispered and what we screamed , "I'm from Idaho" , A knight, errant , The work of sulphur , Waiting for moving water , If i were a woman , Pygmalion , Graduation , The hand of the almighty , Tragedy , A brawling woman in a wide house , Sorcery of physics , The substance of things , West of the sun , Four long arms, whirling , Gambling for redemption , The family, morality, and social science , The princess , Educated.

Fear and loathing in Las Vegas (Colorado State Library Book Club Collection): a savage journey to the heart of the American dream (Vintage Books, 1971)
Records the experiences of a free-lance writer who embarked on a zany journey into the drug culture.

Telling your story (Colorado State Library Book Club Collection) (Fulcrum, 2016)
"Jerry Apps, renowned author and storyteller, believes that storytelling is the key to maintaining our humanity, fostering connection, and preserving our common history. In Telling Your Story, he offers tips for people who are interested in telling their own stories. Readers will learn how to choose stories from their memories, how to journal, and find tips for writing and oral storytelling as well as Jerry's seasoned tips on speaking to a live radio or TV audience. Telling Your Story reveals how Jerry weaves together his stories and teaches how to transform experiences into cherished tales. Along the way, readers will learn about the value of storytelling and how this skill ties generations together, preserves local history, and much more. "--

Full body burden (Colorado State Library Book Club Collection): growing up in the nuclear shadow of Rocky Flats (Broadway Books, 2013)
Full body burden is Kristen Iversen's story of growing up in a small Colorado town close to Rocky Flats, a secret nuclear weapons plant. It's also a book about the destructive power of secrets -- both family secrets and government secrets. Her father's hidden liquor bottles, the strange cancers in children in the neighborhood, the truth about what they made at Rocky Flats -- best not to inquire too deeply into any of it. But as Iversen grew older, she began to ask questions and discovered some disturbing realities. As this memoir unfolds, it reveals itself as a brilliant work of investigative journalism -- a shocking account of the government's sustained attempt to conceal the effects of the toxic and radioactive waste released by Rocky Flats, and of local residents' vain attempts to seek justice in court. Based on extensive interviews, FBI and EPA documents, and class-action testimony, this taut beautifully written book promises to have a very long half-life -- P. [4] of cover.
Mother's Day, 1963 , Drums and bunnies, 1969 , Nuns and pirates, 1974 , Operation Desert Glow, 1979 , A raid and a runaway grand jury, 1989 , Doom with a view, 1990 , Fire, again, 1991-1996 , What lies beneath, 1996-2011.

En el pais amamos (Colorado State Library Book Club Collection): mi familia divida (Henry Holt and Company, 2016)
"Diane Guerrero, the television actress from the megahit Orange is the New Black and Jane the Virgin, was just fourteen years old on the day her parents and brother were arrested and deported to Colombia while she was at school. Born in the U.S., Guerrero was able to remain in the country and continue her education, depending on the kindness of family friends who took her in and helped her build a life and a successful acting career for herself, without the support system of her family. In the Country We Love is a moving, heartbreaking story of one woman's extraordinary resilience in the face of the nightmarish struggles of undocumented residents in this country. There are over 11 million undocumented immigrants living in the US, many of whom have citizen children, whose lives here are just as precarious, and whose stories haven't been told. Written with Michelle Burford, this memoir is a tale of personal triumph that also casts a much-needed light on the fears that haunt the daily existence of families likes the author's and on a system that fails them over and over"-- La estrella de Orange is the New Black y de Jane the Virgin presenta su historia personal acerca de la grave situación en que se encuentran los inmigrantes indocumentados en este país.Diane Guerrero, la actriz de televisión del popular programa Orange is the New Black y de Jane the Virgin, contaba con sólo catorce años cuando un día sus padres y su hermano fueron arrestados y deportados mientras ella estaba en la escuela. Como había nacido en Estados Unidos, Guerrero pudo permanecer en el país y seguir estudiando gracias a la bondad de amigos de la familia, quienes se hicieron cargo de ella y la ayudaron a construir su propio camino y a que se convirtiera en una exitosa actriz de carrera sin tener la red de apoyo de su familia.En el país que amamos es una historia conmovedora y dolorosa sobre la resistencia extraordinaria de una mujer ante las aterradoras luchas que enfrentan los residentes indocumentados de este país. Hay más 11 millones de inmigrantes indocumentados viviendo en Estados Unidos, muchos de los cuales tienen hijos con ciudadanía estadounidense, pero cuya permanencia en este país es tan frágil como la de sus padres y cuyas historias no han sido contadas. Escrita en conjunto con Michelle Burford, esta autobiografía es una historia de triunfo personal que, además, arroja una muy necesaria luz sobre los miedos que permean la vida diaria de familias como la de la autora y sobre un sistema que les falla una y otra vez.
The silver key , Mi familia , Underground , The good girl , The plan , Ground shift , Taken , Left behind , Second family , Butterfly , New world , The edge , Turnabout , Stage right , New York City , Orange , Into daylight , Call to action.

Optimal Distance, a Divided Life: part two (Colorado State Library Book Club Collection) (Camperdown Elm Publishing, LLC, 2017)
"Joan Carol Lieberman's mother developed paranoid schizophrenia shortly after the author's birth in 1942. Her poignant narrative of how she sought optimal distance from her mother's dangerous paranoid impulses is a powerful reminder of the urgent need to find a cure for schizophrenia."

You changed my life (Colorado State Library Book Club Collection): Tu as changé ma vie (Weinstein Books, 2012)
"The highest-grossing non-English-language film of all time, Intouchables reveals the life of a charismatic con man, Abdél Sellou (played by the award-winning actor Omar Sy), whose friendship with a disabled French aristocrat, Philippe Pozzo di Borgo, inspired the record-breaking hit movie. You Changed My Life is Abdel Sellou's memoir of growing up on the streets of Pris as a cheeky young Algerian immigrant, honing his talents as a petty thief and scam artist before meeting the man who would forever change his life, as Abdel would change his. In 1993, Count Philippe Pozzo di Borgo, on the heels of his wife's being diagnosed with a terminal illness, suffered a paragliding accident that left him a quadriplegic. Forty-two years old, trapped inside his luxurious Paris town house, he was an outcast for the first time in his life. Abdel, an unemployed Algerian immigrant who had been an outcast for his entire existence, would become Philippe's unlikely caretaker. Quick-thinking, unsentimental, and more than a little wild, Abdel surprises both himself and his employer by developing an unswerving loyalty - and orchestrating more than a few adventures - that help restore Philippe's appetite for life. The story of Abdel's friendship with Philippe has already touched the hearts of millions. Now his personal story of transformation from a kid who cares for no one to the person he is today will affect many more"--P. [4] of cover.
Paperback , You Saved My Life tells the extraordinary true story of the charming Algerian con-man whose friendship with a disabled French aristocrat inspired the record-breaking hit film, The Intouchables. Sellou's fictional reincarnation, Driss, played to critical acclaim by French comedian Omar Sy in the movie Les Intouchables, captured the hearts of millions with his edgy charm. Already a bestseller in France and Germany, You Changed My Life shows us the real man behind Sy's smiling face. The book takes us from his childhood spent stealing candy from the local grocery store, to his career as a pickpocket and scam artist, to his unexpected employment as a companion for a quadriplegic. Sellou has never before divulged the details of his past. In many interviews and documentaries, he has evaded or shrugged off the question of his childhood and his stay in prison, until now. He tells his story with a stunning amount of talent, with humor, style, and , though he denies that he has any , humility. Sellou's idiosyncratic and candidly charming voice is magnificently captured in this memoir, a fact to which his friend Philippe Pozzo di Borgo testifies in his touching preface for the book.

Beautiful boy (Colorado State Library Book Club Collection): a father's journey through his son's addiction (Mariner Books, Houghton Mifflin Harcourt, 2018)
The story of one teenager's descent into methamphetamine addiction is told from his father's point of view, describing how a varsity athlete and honor student became addicted to the dangerous drug and its impact on his family.
Stay up late , His drug of choice , Whatever , If only , Never any knowing , Epilogue , Afterword.

Come, reza, ama (Colorado State Library Book Club Collection): el viaje de una mujer por Italia, India e Indonesia en busca del equilibrio entre cuerpo y espr̕itu (Aguilar, 2010)
Traces the author's decision to quit her job and travel the world for a year after suffering a midlife crisis and divorce, a journey that took her to three places in her quest to explore her own nature and learn the art of spiritual balance.

Pearl Buck in China (Colorado State Library Book Club Collection): journey to The good earth (Simon & Schuster, 2010)
An engrossing biography of Buck, a woman whose fascinating life gave her a unique outlook on the plight of women and the suffering of China's rural poor.
Family of ghosts , Mental bifocals , The spirit and the flesh , Inside the doll's house , Thinking in Chinese , In the mirror of her fiction , The stink of condescension , Paper people.

The only girl in the world : (Colorado State Library Book Club Collection): a memoir (Little, Brown and Company, 2017)
Describes the author's harrowing upbringing by fanatic parents, who raised her in isolation through traumatic disciplinary exercises designed to "eliminate weakness," and recounts how she eventually escaped with the help of an outsider.

Honey bus (Colorado State Library Book Club Collection): a memoir of loss, courage and a girl saved by bees (Park Row Books, 2020)
Meredith May recalls the first time a honeybee crawled on her arm. She was five years old, her parents had recently split and suddenly she found herself in the care of her grandfather, an eccentric beekeeper who made honey in a rusty old military bus in the yard. That first close encounter was at once terrifying and exhilarating for May, and in that moment she discovered that everything she needed to know about life and family was right before her eyes, in the secret world of bees.

La distancia entre nosotros (Colorado State Library Book Club Collection) (Atria Paperback, 2013)
"Cuando el padre de Reyna Grande deja a su esposa y sus tres hijos atrás en un pueblo de México para hacer el peligroso viaje a través de la frontera a los Estados Unidos, promete que pronto regresará; con el dinero suficiente para construir la casa de sus sueños. Sus promesas se vuelven más difíciles de creer cuando los meses de espera se convierten en años. Cuando se lleva a su esposa para reunirse con él, Reyna y sus hermanos son depositados en el hogar ya sobrecargado de su abuela paterna, Evila, una mujer endurecida por la vida. Los tres hermanos se ven obligados a cuidar de sí mismos. En los juegos infantiles encuentran una manera de olvidar el dolor del abandono y a resolver problemas de adultos. Cuando su madre regresa, la reunión sienta las bases para un capítulo nuevo y dramático en la vida de Reyna: su propio viaje a El otro lado para vivir con el hombre que ha poseído su imaginación durante años-- su padre ausente."--Book cover.